Political Fantasy Literature on HIV/Aids: Regarding the Figure of the Ghost in Fujirazú (2023), by José Ricardo Chaves - Rojas González, José Pablo (2024)
This article focuses on the most recent novel by José Ricardo Chaves, Fujirazú, which takes up the topic of HIV/AIDS. The aim of the paper is to study the gothic fantastic elements present in the novel, specifically the figure of the ghost, which acts politically (the ghost besieges us with its truth), especially in relation to its “revenge for justice” and its “loving possession.” The article concludes with the idea that Chaves’s novel uses gothic elements to invite the reader to explore the spectral dimensions of the policies linked to HIV/AIDS in the 1980s, which were not different from other policies of exclusion and elimination that occurred at other times in history.